NUMERICAL STUDIES ON THE EFFECT OF MOORING LINE MATERIAL ON THE RESTORING BEHAVIOR AND HYDRODYNAMIC RESPONSES OF A FPSO - Batide, Noor Fahmie (Universiti Teknologi PETRONAS, 2021)
The primary function of a mooring system is to safely maintain floating structures within their designed excursion limits.